Navigating Intercultural Communication: Challenges Faced by International Students - Qulub, Muhammad Farihul; Rusmawati, Roosi (Deskripsi Bahasa, 2025)
Cross-cultural communication among international students presents specific strategies and challenges, particularly within the educational domain. The success of communication largely depends on the ability of international students to adapt and develop effective coping mechanisms in the host country. This study aims to investigate the strategies and coping mechanisms employed by international students during their learning experiences in Indonesia. A descriptive qualitative method was applied, involving two international student participants. The findings reveal several challenges in cross-cultural communication, mainly cultural differences that influence both verbal and non-verbal interactions. Data analysis was conducted through triangulation by comparing participants’ experiences with previous studies and relevant theories. This research provides an in-depth analysis of the challenges and coping strategies of international students, highlighting aspects that have not been extensively discussed in previous studies. The results are expected to serve as a valuable reference for future international students in navigating cross-cultural differences within Indonesian educational contexts.